Sloshing in upright circular containers : theory, analytical solutions and applications - Raynovskyy, Ihor; Timokha, A. N. (Boca Raton : CRC Press, 2020)
"This book presents mathematical fundaments and results on sloshing in an upright circular cylindrical tank with semi-analytical solutions. The book outlines generic mathematical and physical aspects of the multimodal method, describes milestones, and presents several versions of modal systems for an upright circular tank, both linear and nonlinear.The book offers an extend description of the state-of-the-art theoretical sloshing with more than 200 references. It presents mathematical fundamentals of free-surface sloshing problems, details linear and nonlinear modal equations, provides analytical estimate of viscous damping, and covers stability analysis of steady-state solution.The book is for engineers dealing with sloshing, applied mathematicians working on free-surface problems, and lecturers in fluid mechanics that need to know the fundamentals and analytical solutions from surface wave theory"--
OCLC-licensed vendor bibliographic record.
Keywords: Sloshing (Hydrodynamics); Storage tanks; TECHNOLOGY / Engineering / Mechanical; TECHNOLOGY / Engineering / Industrial; TECHNOLOGY / Operations Research